Creation of knock out and knock in mice by CRISPR/Cas9 to validate candidate genes for human male infertility, interest, difficulties and feasibility - Kherraf, Zine-Eddine; Conne, Beatrice; Amiri-Yekta, Amir; Kent, Marie Christou; Coutton, Charles; Escoffier, Jessica; Nef, Serge; Arnoult, Christophe; Ray, Pierre F. (Molecular and cellular endocrinology, 2018)
High throughput sequencing (HTS) and CRISPR/Cas9 are two recent technologies that are currently revolutionizing biological and clinical research. Both techniques are complementary as HTS permits to identify new genetic variants and genes involved in various pathologies and CRISPR/Cas9 permits to create animals or cell models to validate the effect of the identified variants, to characterize the pathogeny of the identified variants and the function of the genes of interest and ultimately to provide ways of correcting the molecular defects. We analyzed a cohort of 78 infertile men presenting with multiple morphological anomalies of the sperm flagella (MMAF), a severe form of male infertility. Using whole exome sequencing (WES), homozygous mutations in autosomal candidate genes were identified in 63% of the tested subjects. We decided to produce by CRISPR/cas9 four knock-out (KO) and one knock-in (KI) mouse lines to confirm these results and to increase our understanding of the physiopathology associated with these genetic variations. Overall 31% of the live pups obtained presented a mutational event in one of the targeted regions. All identified events were insertions or deletions localized near the PAM sequence. Surprisingly we observed a high rate of germline mosaicism as 30% of the F1 displayed a different mutation than the parental event characterized on somatic tissue (tail), indicating that CRISPR/Cas9 mutational events kept happening several cell divisions after the injection. Overall, we created mouse models for 5 distinct loci and in each case homozygous animals could be obtained in approximately 6 months. These results demonstrate that the combined use of WES and CRISPR/Cas9 is an efficient and timely strategy to identify and validate mutations responsible for infertility phenotypes in human. •Whole exome sequencing is successful in identifying fertility genes.•Creation of transgenic animals permits to study the pathogeny of the identified genes.•The use of CRISPR/Cas9 is a fast and efficient way to create KO and KI mice.•Mice KO for spermatogenesis genes usually closely reproduce the human phenotype.